Shepherd electron effects in multiple ionization of rubidium by circularly polarized intense laser fields - Shiwei Liu; Difa Ye; Yuhai Jiang; Jie Liu (Communications Physics, 2023)
Abstract Nonsequential double/multiple ionization (NSDI/NSMI) of atoms in strong laser fields is a paradigm system for studying field-intervened electron-electron correlation. However, there exists a long-standing debated topic as to how NSDI/NSMI is triggered in a circularly-polarized laser field. In this contribution, it is shown counter-intuitively that the NSMI of alkali atoms is strongly enhanced due to a mechanism induced by their intrinsic shell structure, coined as the shepherd electron effect. Specifically, we find that the early-released outermost electron (the shepherd electron) can be stabilized on the Rydberg states even after dislodging some other inner-shell electrons and thus lead to the emergence of a transient hollow atom. Experimental signatures of the shepherd electron effect and its real-time observation with the attoclock technique are discussed. These results have substantially enriched our understanding of NSMI, beyond the well-accepted cascade recollision picture. They might have applications in coherent extreme-ultraviolet (XUV) light amplification.